Single-Shot Quantum Nondemolition Detection of Individual Itinerant Microwave Photons - Besse, Jean-Claude; Gasparinetti, Simone; Collodo, Michele C.; Walter, Theo; Kurpiers, Philipp; Pechal, Marek; Eichler, Christopher; Wallraff, Andreas (Physical Review X, 2018)
Single-photon detection is an essential component in many experiments in quantum optics, but it remains challenging in the microwave domain. We realize a quantum nondemolition detector for propagating microwave photons and characterize its performance using a single-photon source. To this aim, we implement a cavity-assisted conditional phase gate between the incoming photon and a superconducting artificial atom. By reading out the state of this atom in a single shot, we reach an external (internal) photon-detection fidelity of 50% (71%), limited by transmission efficiency between the source and the detector (75%) and the coherence properties of the qubit. By characterizing the coherence and average number of photons in the field reflected off the detector, we demonstrate its quantum nondemolition nature. We envisage applications in generating heralded remote entanglement between qubits and for realizing logic gates between propagating microwave photons.
CRIS-Team Scopus Importer:2022-06-27